Borders Reality of Science in the Contemporary World (Subjectivity and Coexistence in Interactive Infinity of Comprehension) - Petrović, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
In humanistic sciences, a method of overcoming given borders of formulated dimensions of being in the world involves both their tightening and their opening for a different outcome. The concept of science is not fixed nor dominant, but represents the plurality of its principal and heuristic definitions, which are unified in its discourse in the articulation of its achievements. By following its heuristic principles and the unity of concept and reality—achieved by deliberating on the phenomenon of existence, science disregards mediocre results. At the borderline areas, there exist a spirit who enables the self-consciousness which in turn enlightens the science. Re-stringing of rules which lead to naïve solipsism implies the constitution of the so-called ‘natural position’ as a certain mode of existence—a transcendental insight into the world of life through self-realization or self-understanding. Experience gained this way is distinguished from mediocre insights and attitudes thus earning the competence of the scientific method to new horizons and original solutions.
Keywords: scientific interest; scientific method; phenomenological structure of world of life; critique of the phenomenological method; hermeneutics of the deeper conceptual structures